Evaluation of Heat Stress Impacts on Physiological Responses in Two Indigenous Nigerian Goats - Tella, Adetunmbi; Dandara, Gazali B; Gabriel, Godfrey O; Oluwadele, Joshua; Osunkeye, Jacob O (Jambura Journal of Animal Science, 2024)
Stress comes in many forms for livestock, including physical, chemical, nutritional, thermal, and psychological stress. Changes in skin temperature, heart rate, respiration rate, and rectal temperature are indicators of physiological reactions to heat stress. Regression investigation of the physiological reactions of Nigerian native goat breeds (West African dwarf and Red Sokoto) to heat stress was the goal of this study. 400 goats (200 West African Dwarf and 200 Red Sokoto) from Osun, Ondo, and Ekiti states in Nigeria were subjected to varying climatic conditions (temperature and humidity) in order to gather data on physiological indicators (rectal temperature, pulse rate, and respiration rate). An analysis of variance (ANOVA) was performed to evaluate variations in the physiological parameters, and the temperature and humidity index (THI) was computed for the study's environmental conditions.  The coefficient of determination (R2), which represents the accuracy of the predictions, was calculated using regression analysis. The results demonstrated that both breeds' physiological characteristics reacted similarly, with higher THI values considerably increasing heart rate, respiration rate, and rectal temperature. Regression evaluation indicated that THI had a significant (P â‰¤ 0.05) and positive effect on heart rate (R² = 0.545), respiration rate (R² = 0.32), and rectal temperature (R² = 0.146) for the Red Sokoto breed. These physiological adaptations enable goats to survive and thrive in challenging and variable environments.